Assessment of community knowledge and perception on environmental issues in Jimma Zone, Southwest Ethiopia - Abebayehu Aticho; Dessalegn Obsi Gemeda; Tariku Mekonnen; Tamiru Chalchesa; Deresa Abetu; Kerryn Morrison; George Archibald (Brawijaya University, 2019)
Environmental knowledge and perceptions of community govern the sustainable use and management of environmental resources. Developing countries such as Ethiopia has been facing serious environmental problems. In spite of the existing problems, little is known about public understanding and perception of environmental issues. Thus, the overall objective of this research was to assess community perception and knowledge of environmental issues. Interview was conducted using structured questionnaire. The collected data was coded, cleaned and analyzed using descriptive and inferential statistics. The result indicates, most of the community members believed that they have better knowledge of environmental issues but the evidence obtained from measured knowledge shows the reverse. The principal source of environmental information (local media broadcasting) had positive correlation with perceived knowledge, and negatively correlated with assessed knowledge and perception index of environmental issues. Correctly answered questions used in the evaluation of environmental knowledge were weekly associated (r < .2) with perceived knowledge and perception, which indicates the respondents lacks same concept on environmental issues. Perceived knowledge was negatively and significantly (P <.001) determined by age and educational levels of respondents. But, measured knowledge was negatively and significantly (P <.05) affects by age, childhood area, education and occupation when positively and significantly (P = .001) influenced by origin of residence. The perception of community was positively and significantly (P =.001) determined by respondent's age, childhood area, education and information source but negatively and significantly (P < .05) influenced by origin of residence and ethnic group. Generally, self-reported knowledge is not reliable source of information for environmental management decisions. So, stakeholders should strongly works on environmental awareness campaigns, engage students in outdoor activities, and training to improve factors negatively determined community's factual knowledge and perception of environment.